Identification of the IL-13 gene rs20541 single nucleotide polymorphism and its association with renal cell carcinoma in Iraqi patients - Dhabaan, Anwar Abed Nasser; Abbas, Hussein Mahmood; Muhammed, Haidar J.; Saleh, Tahreer Hadi (Ukrainian Journal of Nephrology and Dialysis, 2024)
Renal cell carcinoma (RCC) is a common and aggressive form of kidney cancer, with genetic factors playing a significant role in its development. Recent research has focused on the potential involvement of cytokine gene polymorphisms, including those in the interleukin (IL) -13 gene, in RCC susceptibility. The present study aimed to investigate the association between the IL-13 gene rs20541 single nucleotide polymorphism (SNP) and the risk of RCC in Iraqi patients. Methods. A case-control study was conducted involving 250 participants, including 125 patients diagnosed with RCC and 125 healthy controls matched for age and sex. Blood samples were collected from all participants for DNA extraction. The IL-13 gene rs20541 SNP was genotyped using the Tetra-Primer Amplification Refractory Mutation System-Polymerase Chain Reaction (TARMS-PCR) method. Statistical analysis was performed to compare the frequencies of genotypes (GG, GA, AA) and alleles (G, A) between cases and controls, and to evaluate their association with RCC risk. Results. The study found significant differences in the distribution of IL-13 rs20541 genotypes and alleles between RCC patients and healthy controls. The presence of the GG genotype was significantly associated with an increased risk of RCC (OR = 3.7, 95% CI = 2.15–6.37, P = 0.002), while the AA genotype was significantly associated with a protective effect against the disease (OR = 0.38, 95% CI = 0.21–0.69, p = 0.002). On the other hand, the GA genotype did not show a significant association with protection against RCC (OR = 0.6, 95% CI = 0.36–1.00, p = 0.067). For the G and A alleles, the G allele was found to be a highly significant risk factor for RCC (OR = 2.67, 95% CI = 1.85–3.84, p <0.0001), while the A allele was significantly associated with a protective effect (OR = 0.37, 95% CI = 0.26–0.54, p <0.0001). Conclusion. The current study provides evidence that the IL-13 rs20541 SNP, particularly the GG genotype and G allele, may be associated with an increased risk of developing RCC in the Iraqi population. This finding suggests that the rs20541 polymorphism could serve as a potential genetic marker for RCC susceptibility. Further research is needed to confirm these results and to explore the underlying mechanisms of how IL-13 gene polymorphisms contribute to RCC pathogenesis.